Gender and ethnic equity in Aotearoa New Zealand's public service: where is the progress amid the pandemic?. (3rd April 2022) - Parker, Jane; Young-Hauser, Amanda; Loga, Patricia; Paea, Selu
ABSTRACT: While Aotearoa New Zealand's (NZ's) government has sought to encourage diversity in public service agencies via recent regulatory and policy drives, workplace developments have been disrupted by Covid-19. This study draws on a typology of equality approaches to appraise the 'ambition' of equity progress in NZ public service agencies in the pandemic context, based on a thematic content analysis of semi-structured interviews with sector experts, agency staff and managers. Various equity indices indicate that work-related inequities remain more pronounced for Māori and Pasifika women. Furthermore, public service agencies have generally emphasised 'shorter' equality goals in practice, but organisational responses to the pandemic have had nuanced effects on these and more ambitious equity pursuits. However, many sector stakeholders perceive that 'longer', diversity-cognisant equity thinking and measures, supported via multi-lateral efforts, are needed to encourage substantive equity progress for all. Implications of the study's findings are considered in terms of how conventional equity conceptualisations need to be extended and put into practice to reflect processual, cultural, and intersectional dynamics. They will resonate in other countries facing increasing workforce and population diversification.